2020
DOI: 10.1002/cssc.202000818
|View full text |Cite
|
Sign up to set email alerts
|

Chemisorption‐Induced and Plasmon‐Promoted Photofixation of Nitrogen on Gold‐Loaded Carbon Nitride Nanosheets

Abstract: Photocatalytic fixation of nitrogen is a promising method for green conversion of solar light, but has been substantially limited by inefficient activation of the nonpolar N≡N bond and the poor utilization of visible light. In this study, carbon nitride nanosheet composites with abundant nitrogen vacancies and strong plasmonic resonance absorption of visible light have been fabricated through the combination of hydrogen treatment and loading of Au nanoparticles. Ammonia yields of 184 μmol g−1 and 93 μmol g−1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…H2 atmosphere is able to reduce Bi5O7I, Bi2MoO6, and TiO2, creating large amounts of exposed OVs [147][148][149]. NVs were also reported through H2 treatment [52,150,151]. NH3 is also employed as a reducing gas to treat g-C3N4 and generate CVs [152,153].…”
Section: Chemical Reductionmentioning
confidence: 99%
“…H2 atmosphere is able to reduce Bi5O7I, Bi2MoO6, and TiO2, creating large amounts of exposed OVs [147][148][149]. NVs were also reported through H2 treatment [52,150,151]. NH3 is also employed as a reducing gas to treat g-C3N4 and generate CVs [152,153].…”
Section: Chemical Reductionmentioning
confidence: 99%
“…Wu et al. combined activation by nitrogen vacancies and plasmonic resonance absorption of Au nanoparticles on carbon nitride nanosheets for nitrogen conversion in pure water [83] …”
Section: Challenges Of N2 Activationmentioning
confidence: 99%
“…Wu et al fabricated Au‐loaded graphitic carbon nitride (g‐C 3 N 4 ) nanosheets with abundant NVs. [ 58 ] The high concentration of NVs was obtained by calcining nanosheets under H 2 atmosphere. DFT calculations showed that incorporation of Au reduces the NV generation energy from 3.03 to 0.14 eV which further increases the chances of NV formation.…”
Section: Plasmonic Nanomaterials For Nrrmentioning
confidence: 99%
“…Most of the studies utilized a semiconductor (TiO 2 , CeO 2 , Si, Nb-SrTiO 3 , Ag 2 O, (BiO) 2 CO 3 ) in contact with a plasmonic nanomaterial (Au, Ag, Al) to drive photocatalytic NRR. [47,48,[50][51][52][58][59][60][61][62] Incorporation of plasmonic nanostructures allowed to harvest visible light when a wide-gap semiconductor was used. The dominant plasmonenhancement mechanism in metal-semiconductor hybrid system was hot electron injection from the plasmonic metal into the conduction band of the semiconductor.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
See 1 more Smart Citation